Análise de ruído emitido por tratores em regime estacionário e em movimento - Ferreira, Hermes Francisco (2011)
This work deals with the issue of noise in tractors. Considering the great influence of agriculture in brazillian economy, and the knowledge that a great deal of the workforce is employed in this sector, the analysis of the effects of noise on the farm worker is an important aspect to be investigated. To obtain the measurement of noise levels and frequency characteristics is inside the scope of work, as is the presentation of the effects of noise that reaches the ears of the tractor operator. The presentation of a database of noise and its measurement defines the theoretical portion of this work. The practical portion of this work consists in a series of tests in accordance to national and international normative standards.